EMPOWERING PSYCHOLOGICALLY TRAUMATISED CHILDREN AT SCHOOL: THE EXPERIENCE OF SOCIAL PEDAGOGUES - Gudžinskienė, Vida; Karasevičiūtė, Salomėja (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The aim of the study is to reveal the experience of social pedagogues in empowering psychologically traumatised children at school. Qualitative research was chosen for the study by using the method of semi-structured interview. 10 social pedagogues, who work in school in different Lithuanian regions, participated in the study. The study revealed the experience of social pedagogues in empowering traumatised children in school. The study highlighted that in empowering children who have experienced psychological trauma, it is first of all important for the social pedagogue to show the child individual care and provide him with the necessary support. Ensuring that the child receives emotional support and counselling, if necessary using the services of a psychotherapist or psychologist. It is also important to work with the child's family to understand the family's needs and capacity to provide the necessary support. Provide the family with practical help and advice on how to cope with the child's trauma and stress. In order to empower children, it is important to allow them to participate in decision-making because then children will feel in control of their own lives. Empowering psychologically traumatised children requires providing them with a safe and stable environment where they can feel calm and have their needs met. It is equally important that traumatised children become involved in classroom activities or social groups at school, to build relationships and receive support from the school community. Social educators emphasise the importance of educational activities in the school community to help children develop their skills and talents. Long-term collaboration to empower children and their families ensures sustainable well-being of society.